Re-Calling Our HerStory: Miriam the Prophetess - Wouk, Judith Maeryam (Canadian Woman Studies/les cahiers de la femme, 2015)
L’eau a joué un rôle significatif dans la l’histoire de Miriam dans la Bible. Elle surveille son frère au bord de l’eau, elle danse à la Mer, une légende juive l’identifie à un puits et elle est associée symboliquement à la naissance. Miriam comme un modèle ancien, est une inspiration pour les femmes d‘action. Water plays a significant role in the Biblical story of Miriam the Prophetess, the sister of Aaron. She watches her brother Moses by the river, and provides him with a wet-nurse; she leads the dance when the Israelites successfully reach the far shore of the Sea, in Jewish lore a well follows her, and she is symbolically associated with conception and birth. An ancient role model, Miriam is again inspiring women to action.